National Assessment of Achievement of Students Completing Grade 04 in Year 2008 - National Education Research and Evaluation Centre, University of Colombo (University of Colombo, 2008)
1. National Assessment of Achievement of Students Completing Grade 04 in Year 2008 As a member country agreed on the World Declaration on Education for All, Sri Lanka strives to enhance the quality of education by implementing procedures that will provide information on students’ learning. One such measure adopted was monitoring student achievement through two national assessments conducted by the National Education Research and Evaluation Centre (NEREC), at Grade 04 level in 2003 and 2007 respectively. According to the findings of the 2007 study, during the four years from 2003 to 2007 a considerable improvement in achievement can be seen. Although there is a substantial increase in achievement over the period, there was a need to find out whether this trend is sustained. Therefore, the present study conducted in 2009 by NEREC was to find out whether the positive trends observed over time is sustained and to identify areas for further improvement. Students who had completed fourth grade in the education system of Sri Lanka in the year 2008 were considered as the desired target population of this study. The sample procedure had a multi stage approach. In the first stage schools were selected for the sample. Schools were selected within strata with Probability Proportional to Size, without replacements. In the second stage a group of students were selected from the sampled schools using cluster sampling approach. An entire grade 04 class from each sampled school was selected. Province was taken as explicit strata. The medium of instruction and school type were considered as the implicit stratum. In the 2009 study five achievement tests were used like in the 2007 study as instruments to assess student achievement. That is tests in Sinhala language, English language, Tamil language, English Language and “TIMSS” (Trends in International Mathematics and Science Study). In 2009, the Sri Lankan version of TIMSS was revised to include 40 items. The construct assessed in these studies had been the essential learning competencies that were expected to be achieved by Grade four students at the end of Key Stage II. Based on these competencies Tables of specifications were prepared for each subject to maintain content validity. Data gathered through the achievement tests were analysed on a national and provincial basis in relation to medium of instruction, school type, location and gender. Patterns and trends in learning achievement were discussed using three indicators mean, standard deviation and skewness values. The findings revealed that while the patterns of achievement identified in the previous studies continue there were also changing patterns. The shift from the Western province being the highest performing province to North Western is one such change. On the other hand, while student performance in Sinhala as a first language is high, the achievement in Tamil as a first language is moderate and achievement in English language is satisfactory. Further, increasing trend observed over time in all subjects (except in TIMSS) is positive. Improved performance in students in Type 2 schools and rural schools is also another positive trend. However, there are negative trends that policy makers need to focus attention. Continuous low performance of Northern, Eastern and Uva province, declining performance of male students, especially in mathematics and low performance in some provinces in English are some of these negative trends.